2023
DOI: 10.1002/pan3.10526
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and potential of agri‐environmental schemes in Europe: Cross‐regional evidence from interviews with farmers

Bartosz Bartkowski,
Michael Beckmann,
Marek Bednář
et al.

Abstract: In Europe and elsewhere, agri‐environmental schemes (AES) are designed to reduce agriculture's impacts on the environment. Designing effective schemes requires an understanding of the reasons that drive farmers' decisions whether to adopt AES. Currently, most insights come from individual case studies or structured surveys based on predefined questions. There is a paucity of studies that do not rely on rigid preconceptions about relevant behavioural factors while also offering a geographically and socio‐cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…biodiversity conservation; Gailhard and Bojnec 2015), and production-specific (Sattler and Nagel 2010). Although it could be expected that large agri-businesses focused on high-intensity management and for-profit crop production may less likely engage in agri-environment programmes, previous studies have shown that greater profit margins, sufficient administrative capacity and a larger area of managed land allow higher AEP uptake in these types of farms, while AEPs are perceived as a form of income diversification (Paulus et al 2022, Bartkowski et al 2023.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…biodiversity conservation; Gailhard and Bojnec 2015), and production-specific (Sattler and Nagel 2010). Although it could be expected that large agri-businesses focused on high-intensity management and for-profit crop production may less likely engage in agri-environment programmes, previous studies have shown that greater profit margins, sufficient administrative capacity and a larger area of managed land allow higher AEP uptake in these types of farms, while AEPs are perceived as a form of income diversification (Paulus et al 2022, Bartkowski et al 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Another notable trend that emerged from our analysis is that economically small farms across most farm specialisations are the ones that are the most unlikely to engage in any AEP (figures 4, 5; tables A9 and A10). Apart from the lack of administrative capacity (Wittstock et al 2022, Bartkowski et al 2023, some possible explanations may be the absence of suitable land parcels (Pavlis et al 2016) and insufficient outreach by policy-makers towards small farms to adopt agri-environment measures (Coyne et al 2021). The availability of advisory services, combined with low bureaucratic burdens, proved highly relevant to increasing AES adoption (Massfeller et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations